Sistem Pendukung Keputusan Pemilihan Mitra Jasa Pengiriman Barang menggunakan Metode Simple Additive Weighting (SAW) - Technique for Other Reference by Similarity to Ideal Solution (TOPSIS) di Kota Malang - Lisa Septian Putri; Nurul Hidayat; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Malang is a big city that develops in East Java, so it is not surprising that there are many freight forwarding partners that offer freight services to the public. Where most of the average of the goods delivery partner is its reach not only in Malang alone but nationally and even internationally. Thus, many people are still confused to choose which shipping service partners are best seen from the characteristics of the goods such as easily broken, fragile, large dimensions and so on. So it raises the risk when the process of delivery of goods. So, it is necessary to build a system that can help the community in taking a decision. The model used to build this Decision Support System uses Fuzzy Multiple Atribute Decision Making (FMADM) with Simple Additive Weighting (SAW) method- Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). It is hoped that the decision will be more objective, so that the selected partners will meet the needs of the community and minimize the mistakes. Accuracy calculation results from 7 data comparison of actual results data with target data results of 28.57% and comparison of actual results data with target results of 71.42%. And the value of Usability Testing from 20 respondents obtained the result of 71.66% of questions able to answer, the percentage of 28.33% of questions can not be answered by the respondents, from these results can be concluded that the android application is declared good.